Efforts To Increase The Effect Of The Disciplinary Development Program In The Teaching And Learning Process On The Independent Work Ethic Of Teachers At SD Negeri 026 Rambah, Rambah District, Rokan Hulu Regency - Agus Syaifudin Jufri (STKIP Rokania Pasir Pangaraian, 2022)
This study aims to determine whether there is an increase in interest in learning mathematics in class VI students of 003 Kunto Darussalam Public Elementary School through the Application of Cooperative Learning Techniques of Sending Greetings and Questions. In this study, the formulation of the problem was How to Increase Students' Interest in Learning Mathematics Through the Application of Cooperative Learning Techniques of Sending Greetings and Class VI Questions at Public Elementary School 003 Kunto Darussalam on the subject of fractional arithmetic operations. This research was a classroom action research. The subjects in this study were grade VI students of SD Negeri 003 Kunto Darussalam and the object was the application of cooperative learning techniques of sending greetings and questions to increase students' interest in learning mathematics. The research begins with an initial meeting (without action) and three cycles (with action). The data collection technique in this study was once before the action, the researcher made initial observations during the learning process by filling in the interest observation sheet, then the researcher applied cooperative learning techniques by sending greetings and questions, and observing the development of student interest by filling out the observation sheet. Based on this analysis, it can be concluded that there is an increase in interest in learning mathematics for class VI students of SD Negeri 003 Kunto Darussalam through the application of cooperative learning techniques by sending greetings and questions